SEJARAH UPACARA GAREBEG KRATON NGAYOGYAKARTA HADININGRAT - . Maharsi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
This paper will examine how the historical development of Garebegceremony, the ceremony began early during the emergence of the Islamic kingdom of Demak NCO reached the age Ngayogyakarta Hadiningra today. Long before Islam developed in this region, Javanese Hindu Kings used to perform a wide variety of religious ceremonies. At the time of the founding of the Kingdom of Demak NCO as an Islamic kingdom in Java, Raden Patah with the support of the trustees maintain a ceremonial monarch Medha to implement Islam. Through the ceremony, the Muslim missionaries tried to incorporate Islamic values in the lives of the people of Java. In the development of ceremonies that changed its name to sekaten the ebb and flow along with the political dynamics of the Islamic kingdoms in Java. After the kingdom of Demakkingdom was replaced by Pajang, there is no evidence showing that theceremony was performed by the Sultan sekaten Hadiwijaja. Even gamelan sekaten as one sekaten ceremony supplies were transferred to the Kingdom of Cirebon. Raden Patah daughter who is married to a descendant of Sunan Gunung Jati is precisely that utilizes gamelan for the propagation of Islam in our region and surrounding areas. During the Islamic Mataram Kingdom in the reign of Sultan Agung, the ceremony sekaten experiencing tremendous growth.Efforts to strengthen the Power of Sultan Agung of Mataram dynasty is held back a religious ceremony that is Sekaten Javanese Islamic kingdom. Sekatenceremonies that have been held since the days of the founding of the Kingdom of Demak NCO and a means of propagation of Islam is revived with a variety of reforms. In the reign of Sultan Agung, Sekaten ceremony held more festive with various reforms, one of them with two new sekaten gamelan Gamelan Kyai Guntur Madu and Kyai Guntur Sari. Sekaten other ceremonial paraphernalia also was renewed at the time of Sultan Agung is the shape and number of the king's alms. Along with the advent of colonization by European nations in Java,Sekaten ceremony also undergone various changes. Various equipment more simple ceremony, while the parties involved are added. Similarly,when the Islamic kingdom in Java was broken into two, Surakarta andYogyakarta Sultanate. Each develops its own royal ceremony held to mark the Muslim religious holidays. Based on the historical analysis is done, the Sultanate Ngayogyakarta want to continue the tradition ceremony during Sultan Agung  Garebeg by accentuating the sides of his Islam. One example is that there are 5 that there are mountains in the Sultanate Ngayogyakarta Garebeg ceremony, likely has existed since the time of Sultan Agung. Given the number of digits has meaning 5 pillars of Islam which is upheld by Sultan Agung.Keywords: Grebeg, Sultan Agung, the Sultanate Ngayogyakarta